Negotiation and groups - Mannix, Elizabeth A., 1960-; Neale, Margaret Ann.; Overbeck, Jennifer R.; Emerald eBooks (Bingley, U.K. : Emerald, 2011)
Negotiation is a process that permeates our everyday lives. From international conflicts to corporate mergers, from labor contracts to distribution agreements, and from one-time job offers to the day-to-day of relationships, negotiation is one of the most common ways to reach agreement on disputed issues and resources. Though negotiation is challenging in the simplest of circumstances, a group context can make it even more complex: groups negotiating with other groups may argue among themselves; factions and coalitions may develop, leading to side deals or the obstruction of deals in progress; the interests and preferences of all parties become much harder to identify, much less satisfy. In this fourteenth volume of the Research on Managing Groups and Teams series, nine chapters examine the particular challenges, opportunities, and dynamics that confront groups engaged in negotiation. The volume will be of particular interest to readers and scholars from management, psychology, sociology, communications, law, political science, and public policy.
ch. 1. When are teams an asset in negotiations and when are they a liability? / Taya R. Cohen, Leigh Thompson -- ch. 2. Physical distance in intragroup and intergroup negotiations : implications for negotiator judgment and behavior / Marlone D. Henderson, Robert B. Lount -- ch. 3. Building multiculturally shared mental models (MSMM) in multiparty negotiations : a three-stage process model / Wendi L. Adair, Leigh Anne Liu -- ch. 4. Games groups play : mental models in intergroup conflict and negotiation / Nir Halevy, Eileen Y. Chou, J. Keith Murnighan -- ch. 5. Status conflict in negotiation / Yeri Cho, Jennifer R. Overbeck, Peter J. Carnevale -- ch. 6. The impact of implicit negotiation beliefs on motivation and cognition in group negotiation / Michael P. Haselhuhn, Laura J. Kray -- ch. 7. Beyond valence : effects of group emotional tone on group negotiation behaviors and outcomes / Meagan K. Peters, Naomi B. Rothman, Gregory B. Northcraft -- ch. 8. Modeling group negotiation : three computational approaches that can inform behavioral sciences / Nazli Turan, Miroslav Dudik, Geoff Gordon, Laurie R. Weingart -- ch. 9. Negotiating within groups : a psychophysiological approach / Frank R. C. de Wit, Karen A. Jehn, Daan Scheepers -- Concluding remarks setting the scene : the calculus of agreement in group negotiation / Gregory B. Northcraft.
Keywords: Business & Economics -- Human Resources & Personnel Management; Business & Economics -- Leadership; Business & Economics -- Workplace Culture; Joint ventures; Business negotiation; Negotiation in business; Teams in the workplace -- Management; Electronic books